Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1440-1746.2005.03866.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection, endoscopic gastric findings and dyspeptic symptoms among a young Japanese population born in the 1970s

Abstract: It is suggested that in consideration of its recent low prevalence and the slow increase in its infection, the prevalence of H. pylori-related gastritis will gradually decrease in Japan. Further studies will be required to ascertain if there is a need for H. pylori eradication in this young population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 48 publications
(54 reference statements)
1
37
0
1
Order By: Relevance
“…18 Some reports have described that dyspeptic symptoms were more frequent among H. pylori-positive patients. 19,20 Although changes in gastric acid secretion by H. pylori infection or functional abnormalities in gastric movement might contribute to dyspepsia, the relationship between them has not been fully clarified. Few reports have described the prevalence of H pylori with dyspepsia in a hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…18 Some reports have described that dyspeptic symptoms were more frequent among H. pylori-positive patients. 19,20 Although changes in gastric acid secretion by H. pylori infection or functional abnormalities in gastric movement might contribute to dyspepsia, the relationship between them has not been fully clarified. Few reports have described the prevalence of H pylori with dyspepsia in a hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although some reports have shown that H. pylori-positive patients tend to have dyspepsia [10,11], the relationship between H. pylori infection and dyspepsia is controversial. The prevalence of H. pylori in Japan has been decreasing with steady improvements in sanitary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of H. pylori in Japan has been decreasing with steady improvements in sanitary conditions. Moreover, some reports have shown using endoscopy that H. pylori-negative patients do not have structural abnormalities [10]. The 2005 American College of Gastroenterology (ACG) guidelines for the management of dyspepsia [12] recommend tests for H. pylori infection among dyspeptic patients without alarm features as well as among H. pylori-positive patients, and proton pump inhibitors for H. pylori-negative patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cancer-preventive effect of eradication therapy may be prominent at the stage when the host's gastric mucosa shows a non-neoplastic or premalignant status. In Japan, the prevalence of H. pylori infection is markedly decreasing and the prevalence at a younger age (<20 years) has fallen below 10% [19]. In addition, the spread of eradication therapy and elucidation of infection routes should accelerate the decreasing trend of H. pylori infection.…”
Section: Cancer Prevention Program In the Next Stepmentioning
confidence: 99%